Paul and his rivals: apostleship and antagonism in the Corinthian correspondence - Mesick, Clair E. (Beihefte Zur Zeitschrift Für Die Neutestamentliche Wissenschaft Series, 2024)
Intro -- Acknowledgments -- Contents -- Part One: The Rival Apostles at Corinth -- Chapter 1: A New Hypothesis on the Rivals of 2 Corinthians -- Chapter 2: The Rival Apostles in the History of Interpretation -- Chapter 3: Apostles, Teachers, and Rivals in the Corinthian Correspondence -- Part Two: Reading 1 Corinthians as the Root of the Conflict -- Chapter 4: Authority and Apostleship in the Corinthian Conflict -- Chapter 5: Financial Malpractice in the Corinthian Conflict -- Chapter 6: Jewish Identity in the Corinthian Conflict -- Conclusion -- Bibliography -- Subject Index -- Index of Ancient Sources.